Pendekatan Stakeholder dalam Pemikiran Etika Bisnis - Nur Lailah (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2009)
Business activities are always perceived as an effort to gain as much as possible profit even if to achieve those steep profits certain unethical or even illegal activities must be done. Examples of such activities are selling low quality merchandises, ignoring customer services, selling merchandises which are not the same to those in advertisements, forcing acquisition of other companies, doing fraud business and s forth.It turns out that those unethical means may results in the collapse of a business or at least no lasting for long time. Therefore, professionalism and business ethic are necessary. Among important aspects of professionalism and business ethics are doing business seriously to produce good quality products, commitment and responsibility without any intention to harm others. In addition, a good businessman should maintain good relationship with distributors, partners, consumers, suppliers, share holders, social workers, media, foreign governments, local governments, local community and so on. This approach is known as stakeholder approach in business ethics.